The Influence of Transformational Leadership, Interpersonal Communication, and Job Satisfaction on Organizational Commitment (A Survey at the Islamic Higher Education Institution in Province of Jambi) - Muhsinin, Umil; Martinis Yamin; Hidayat Hidayat (Dinasti Publisher, 2024)
The high interest of the community in pursuing higher education in Islamic institutions certainly needs to be supported by effective educational management. This is to ensure that Islamic Higher Education institutions in the Jambi Province can compete and produce quality graduates. This research aims to examine the influence of transformational leadership style, interpersonal communication, and job satisfaction on the organizational commitment of lecturers, both partially and simultaneously, as well as directly and indirectly. This quantitative research employed a survey method conducted at the Islamic College (STAI) in the Jambi Province, with a population of 144 lecturers. The analysis tool used Path Analysis followed by Determination Analysis (R Square), Hypothesis Testing with t-tests and F-tests, and a significance level of alpha 5 percent. The results of the study indicate that: 1) Transformational leadership style has an effect on job satisfaction with a t-value of 3.261; 2) Interpersonal communication affects job satisfaction with a t-value of 3.958. 3) Transformational leadership style and interpersonal communication simultaneously affect job satisfaction with an F-value of 67.198; 4) Transformational leadership style influences organizational commitment with a t-value of 5.035; 5) Interpersonal communication affects organizational commitment with a t-value of 4.088; 6) Transformational leadership style and interpersonal communication simultaneously influence organizational commitment with an F-value of 107.340; 7) Job satisfaction influences organizational commitment with a t-value of 11.213; 8) Transformational leadership style, interpersonal communication, and job satisfaction simultaneously influence organizational commitment with an F-value of 83.408; 9) Transformational leadership style through job satisfaction affects organizational commitment; and 10) Interpersonal communication through job satisfaction affects organizational commitment. Based on these findings, the better the Transformational Leadership Style, Interpersonal Communication, and Job Satisfaction of lecturers, the higher the Organizational Commitment of lecturers will be.